Urgensi wawasan poligami sebagai upaya perlindungan hak-hak perempuan - Rahmadani, Karina Aning (Maliki Interdisciplinary Journal, 2024)
This article aims to analyze and discuss in more depth in depth about how te concept of polygamy to realize women’s rights and socialization steps that can provide insight to husband and wives. Socialization steps that can provide insight to husband and wives. This analysis refers to the Marriage Law Article 3 paragraph 1 and QS. An-Nisa’ verse 3. Insight polygamy is very important in practice as an effort to protect women’s rights. Basically, polygamous husband still lack insight. With this paper, it is hoped that polygamous husband will be able to provide women’s rights as wives. And husband do not abuse the notion of polygamy only as a sexual need.